Cultural adaptation, translation and validation of the conflict in adolescence dating relationship inventory (CADRI) in the Greek language - Esperanza Barroso-Corroto; Juan Manuel Carmona-Torres; José Alberto Laredo-Aguilera; Ángel López-Fernández-Roldan; Carlos Navarrete-Tejero; Evangelia Kartsoni; Antonios Christodoulakis; Athina Patelarou; Michail Zografakis-Sfakianakis (PLoS ONE, 2025)
Background Dating violence (DV) is a major public health problem with serious consequences for the young population. The Conflict in Adolescent Dating Relationship Inventory (CADRI) is the most internationally used tool to measure DV. However, no tool has been translated, culturally adapted, or validated in the Greek context to assess the prevalence of DV in the Greek population. Aim To culturally adapt, validate, and translate the Conflict in Adolescent Dating Relationship Inventory (CADRI) in the Greek language to ensure its reliability and cultural and linguistic validity in the Greek population. Methods A cross-cultural adaptation process and cross-sectional study were carried out. There were two phases in the research. First, face validity was assessed after the first phase of translation, which included cross-cultural item adaptation, content validation and expert review of the instrument. In the second stage, the scale’s psychometric qualities were assessed on a sample of nursing college students. A CADRI instrument was used to assess DV. Results The final sample comprised a total of 177 university students. The internal consistency and reliability were good (>0.7), with a Cronbach’s alpha of 0.889 for the violence perpetrated subscale and 0.925 for the violence suffered subscale, indicating strong correlations between the total item scores. After exploratory factor analysis was performed, the structure obtained was similar to the original structure. Furthermore, 88.7% of university students perpetrated DV in the last year on their partners, and 90.7% suffered DV, with verbal and emotional violence the most common types. Conclusion This study provides robust evidence of the validity and reliability of the CADRI for measuring DV in the Greek university population. Additionally, the high prevalence makes it necessary to create DV prevention plans and further research, especially among nursing students. Impact Validation of the CADRI in Greece will increase the knowledge of DV in this population, which lacks validated instruments. Public contribution The results obtained with the CADRI can be applied to the prevention of DV in young people.